P-195 'palliative critical care': transforming the relationship between intensive care and palliative care. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Crispin, Helen; Davis, Carol; Chambers, Robert; Haynes, Karen
Abstract : Introduction: Historically, joint-working between our General Intensive Care Unit (GICU) and Hospital Specialist Palliative Care Team (HSPCT) was restricted to occasional complex cases. In 2013 there was shared recognition that patients, families and staff might benefit from a broader, structured, collaborative approach. In 2014, we created four hours dedicated intensivist time and enhanced joint working – 'Palliative Critical Care'. In 2016, a weekly combined ward round was established. Here, we report the impact of this Quality Improvement Initiative on HSPCT activity and place of care. Methods: Retrospective review of HSPCT records between April 2013 and March 2018. Results: Over 300 patients have been seen under this collaborative model since April 2013. Initially, referrals increased from six in 2013/14 to 57 in 2014/15. Continuous development has resulted in sustained year on year increase in referrals; 107 in year 5 (2017/18). Collaborative working has promoted recognition and treatment of symptoms, and provided an additional layer of support for patients, families and staff. Staff report increased confidence especially in symptom control of actively dying patients. The in-hospital mortality of this patient group is 46%–74% with an ICU mortality of 23%. Patient preferences have been supported; 61.5% of survivors were discharged home or to a hospice (2017/18). In selected cases discharge has been achieved direct from GICU; seven patients to a hospice and eight to home (2013/14 – 2016/17). Patient, family and staff feedback has been 'excellent'; one relative said ' I had no idea that palliative care and intensive care could work together especially for someone who doesn't have cancer and isn't dying! ' Conclusion: Through this Quality Improvement initiative the relationship between our GICU and HSPCT has been transformed from one of occasional interaction to a regular programme of collaborative working resulting in a sustained increase in referrals and supported patient preferences.